The tendency of the schematic structure to maintain stability can be interpreted as mental inertia - Wei, Berlyne (Frontiers in Psychology, 2023)
This paper incorporates schematic concepts related to mental inertia and provides an avenue for interpreting psychology using the principles of classical mechanics. Schemas find wide application in diverse fields, ranging from ergonomics to psychotherapy. Nonetheless, it is crucial to incorporate schemas themselves into a more unified and comprehensive theoretical framework. Drawing upon the free energy principle (FEP) and the second law of thermodynamics, it is evident that humans possess a natural inclination to construct and maintain consistent cognitive structures. This characteristic contributes to the stability of schemas within a defined range. The particular scope of the model is closely intertwined with its structure, leading to variations among individuals in diverse environments. The coherence of the schema within a defined range can be perceived as the magnitude of mental inertia. This psychological analogy emphasizes the importance of considering the influences exerted by the external environment and their effects on mental inertia when predicting the human mind and behavior.